Systems agriculture: modeling and control based on social and economic attributes of agriculture - Mengzhen KANG; Hequan SUN; Xiujuan WANG; Fei-Yue WANG (智能科学与技术学报)
With the arrival and development of the fifth industrial revolution, biotechnology, information technology and artificial intelligence are deeply integrated.This provides strong support for the informatization and intelligentization of agriculture.Due to the social and economic characteristics of agriculture, it has become a consensus to build an agricultural physical and social information system toward both the planting system with biophysical properties and the management system with socio-economic properties.Inspired by systems biology, systems agriculture was proposed, which combined two other dimensions of villages and farmers information using the parallel agriculture framework to build and study the agricultural system.Supported by biotechnology, information technology and artificial intelligence technology, systems agriculture had involved monitoring and integrating multi-scale, multi-dimensional and multimodal information, and carried out systematic research covering agriculture, villages and farmers using systems theory, in order to serve the development of future villages.The intelligent technology and the specific cases involved in systems agriculture were summarized and analyzed, and the perspectives of systems agriculture were presented.